HISTORICAL-ETYMOLOGY RESEARCH OF THE NAMES OF SACRED PLACES USED IN THE WORK HISTORY OF FERGANA (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study analyzes onomastic units recognized as sacred places in Is'hoqkhon Ibrat's "History of Fergana". The etymological, semantic, and grammatical features of necronyms, ekklesionims, and other sacred place names are studied using diachronic, synchronic, and contextual research methods.